Preliminary Phytochemical and Biological Investigations on Different Fractional Extracts of Sarcochlamys pulcherrima (Roxb.) Leaves (Bangladesh Pharmaceutical Journal, 2025)
The current study aimed to investigate the phytochemicals and anti-inflammatory, antioxidant, thrombolytic, and membrane stabilization properties of the Sarcochlamys pulcherrima (Roxb.) leaves by using various fractional extracts. The present study found alkaloids, tannins, flavonoids, reducing sugar, gums, and amides in its hydroalcoholic extract; flavonoids and saponins in its chloroform extract; and steroids and amides in its n-hexane extract. The maximal inhibition values were found for the hydroalcoholic and chloroform fractions in the antioxidant test at a dosage of 100 µg/ml. In addition, at 500 µg/ml concentration, all three extracts demonstrated substantial activity in the anti-inflammatory test accounted for 89.1%, 88.5%, and 82.8% for hydroalcoholic, chloroform, and n-hexane extracts, respectively, compared to the 95.9% for standard (Diclofenac-Na) at the same concentration. In case of thrombolytic activity, the tested extracts showed very weak clot lysis compared to the reference standard, streptokinase. In the membrane stabilization activity test, hydroalcoholic, chloroform, and n-hexane extracts were found to be 52.67%, 50.21%, and 15.52% at 1000 µg/ml, respectively. In comparison, the standard (Aspirin) showed 67.11% at 1000 µg/ml. Thus, overall findings suggested that the hydroalcoholic and chloroform extracts possess significant membrane-stabilizing activity at 1000 µg/ml. Bangladesh Pharmaceutical Journal 28(1): 63-69, 2025 (January)